2015
DOI: 10.1093/aobpla/plv009
|View full text |Cite
|
Sign up to set email alerts
|

Brassinosteroids alleviate high-temperature injury in Ficus concinna seedlings via maintaining higher antioxidant defence and glyoxalase systems

Abstract: Brassinosteroids play a significant role in the amelioration of various biotic and abiotic stresses. To investigate the effects of exogenously applied brassinosteroids on the thermotolerance of plants, reactive oxygen species (ROS), antioxidant defense and methylglyoxal (MG) detoxification systems were examined in Ficus concinna seedlings with or without 24-epibrassinolide (EBR) application. Our results showed that EBR treatment reduced high temperature-induced increases in the levels of ROS, MG and lipid pero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 63 publications
(58 reference statements)
1
25
0
Order By: Relevance
“…β-aminobutyric acid treatment increased the Gly I and Gly II levels in salt treated rapeseed plants, which induces MG detoxification. However, the glyoxylase system composed of Gly I and Gly II regulates the enhanced production of MG under various environmental stresses including salinity [55,56], drought [20,57,58], toxic metals [59,60] and heat exposure [61,62]. Previously, Reddy and Sopory [63] observed that overexpression of the Gly I gene decreased the endogenous MG and enhanced the tolerance against MG and salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…β-aminobutyric acid treatment increased the Gly I and Gly II levels in salt treated rapeseed plants, which induces MG detoxification. However, the glyoxylase system composed of Gly I and Gly II regulates the enhanced production of MG under various environmental stresses including salinity [55,56], drought [20,57,58], toxic metals [59,60] and heat exposure [61,62]. Previously, Reddy and Sopory [63] observed that overexpression of the Gly I gene decreased the endogenous MG and enhanced the tolerance against MG and salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, 24-epibrassinolide (1 mg dm -3 ) pre-treatment further enhanced SOD, POD, CAT and APX activities. 24-Epibrassinolide also alleviated the high temperature-induced oxidative stress by increasing the enzymatic and non-enzymatic antioxidant and glyoxalase systems in seedlings of Ficus concinna (Jin et al 2015). On the other hand, no effect of 24-epibrassinolide (1 μM) on the activity of antioxidative enzymes was observed in heat-exposed tomatoes (Mazorra et al 2011), which suggests that the effect of BRs may be species or cultivar dependent.…”
Section: Mobilization Of Cellular Antioxidant Systemmentioning
confidence: 93%
“…The BR-induced pulse of H 2 O 2 production via NADPH oxidase results in enhanced ABA biosynthesis, which results in further escalation of H 2 O 2 levels leading to prolonged stress tolerance ( Zhou et al, 2014 ). There are many reports showing BR-induced stress tolerance by regulating the activity and expression of antioxidant enzymes ( Cui et al, 2015 ; Jin et al, 2015 ; Sharma et al, 2015 ). This is further supported by the fact that reduced BR biosynthetic mutant plants have reduced ratios of glutathione/glutathione disulfide (GSH/GSSG) and ascorbic acid/dehydroascorbic acid (AsA/DHA), while BR treatment enhances the activity of antioxidant enzymes, expression of various defense-related genes and the GSH/GSSG and AsA/DHA ratios ( Sharma et al, 2012 , 2013a , c ; Zhou et al, 2014 ).…”
Section: Role Of Brs At Physiological and Biochemical Levelmentioning
confidence: 99%